Testicular expression of TDRD1, TDRD5, TDRD9 and TDRD12 in azoospermia - Emad Babakhanzadeh; Ali Khodadadian; Saadi Rostami; Iraj Alipourfard; Mohsen Aghaei; Majid Nazari; Mehdi Hosseinnia; Mohammad Yahya Vahidi Mehrjardi; Yalda Jamshidi; Nasrin Ghasemi (BMC, 2020)
Abstract Background Tudor domain-containing proteins (TDRDs) play a critical role in piRNA biogenesis and germ cell development. piRNAs, small regulatory RNAs, act by silencing of transposons during germline development and it has recently been shown in animal model studies that defects in TDRD genes can lead to sterility in males. Methods Here we evaluate gene and protein expression levels of four key TDRDs (TDRD1, TDRD5, TDRD9 and TDRD12) in testicular biopsy samples obtained from men with obstructive azoospermia (OA, n = 29), as controls, and various types of non-obstructive azoospermia containing hypospermatogenesis (HP, 28), maturation arrest (MA, n = 30), and Sertoli cell-only syndrome (SCOS, n = 32) as cases. One-way ANOVA test followed by Dunnett's multiple comparison post-test was used to determine inter-group differences in TDRD gene expression among cases and controls. Results The results showed very low expression of TDRD genes in SCOS specimens. Also, the expression of TDRD1 and TDRD9 genes were lower in MA samples compared to OA samples. The expression of TDRD5 significantly reduced in SCOS, MA and HP specimens than the OA specimens. Indeed, TDRD12 exhibited a very low expression in HP specimens in comparison to OA specimens. All these results were confirmed by Western blot technique. Conclusion TDRDs could be very important in male infertility, which should be express in certain stages of spermatogenesis.